Ni-catalysed reductive arylalkylation of unactivated alkenes - Jin, Youxiang (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
In this protocol Ni-catalysed reductive arylalkylation of unactivated alkenes tethered to aryl bromides with primary alkyl bromides has been accomplished, providing a new path to construct diverse benzene-fused carbo- and heterocyclic cores including indanes, tetrahydroisoquinolines, indolines and isochromanes. Notably, this new method circumvents the pregeneration of organometallics and demonstrates high tolerance to a wide range of functional groups. The preliminary mechanistic investigations suggest a reaction pathway with an intermediate reduction.